Penguatan Karakter Religius melalui Tradisi Maulid: Analisis Holistik Berbasis Aswaja an-Nahdliyah - Asfaroni, Asfaroni; Subaidi, Subaidi (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
This article discusses the strengthening of religious character education through the tradition of commemorating the birthday of the Prophet Muhammad SAW with a holistic approach based on the Risalah Ahlussunnah wal Jama'ah An-Nahdliyah. This study aims to analyze the role of the Maulid tradition as a means of internalizing the values of faith, sharia, and morals in forming a strong, harmonious, and integrity-based religious character. The research method used is qualitative with a case study, including data collection through interviews, participatory observation, and literature study. The results of the study show that the Maulid tradition is effective in strengthening religious character education by combining spiritual, social, cultural, and psychological aspects comprehensively. This tradition not only strengthens the spiritual bonds of the Nahdliyyah community, but also fosters values of moderation, tolerance, compassion, and social responsibility that are contextual to community life. In conclusion, the commemoration of the Prophet Muhammad's birthday is a strategic medium for Islamic character education that is sustainable and relevant to the challenges of the times, especially in building a generation with character based on the Risalah Ahlussunnah wal Jama'ah An-Nahdliyah